2008
DOI: 10.1007/s11999-008-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence of Disease after Unplanned Excisions of High-grade Soft Tissue Sarcomas

Abstract: Level II, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
130
4
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 48 publications
(124 reference statements)
16
130
4
13
Order By: Relevance
“…1 However, sometimes, unplanned resections are carried out because surgeons fail to consider sarcoma. Unplanned resection is defined as resection of presumed benign masses without appropriate pre-operative imaging, biopsy or attention to surgical margins.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, sometimes, unplanned resections are carried out because surgeons fail to consider sarcoma. Unplanned resection is defined as resection of presumed benign masses without appropriate pre-operative imaging, biopsy or attention to surgical margins.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies emphasize the problems of an unplanned excision showing the higher incidence of local recurrence even after additional surgery [12] or residual tumor in reexcision specimens [2,3,11,17]. Several studies have evaluated the disease-specific survival, metastasis-free survival, and local recurrence-free survival of the patients with unplanned excisions for musculoskeletal tumors in comparison to the patients with planned excisions [8,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the disease-specific survival, metastasis-free survival, and local recurrence-free survival of the patients with unplanned excisions for musculoskeletal tumors in comparison to the patients with planned excisions [8,12,16]. One of these studies suggested patients with unplanned excision followed by additional wide resection had as good or better disease-specific and metastasis-free survival compared with those with planned excision [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whether patients undergoing unplanned excision of their primary sarcoma have a higher risk of local recurrence is controversial [2,4,10,13]. Several studies suggest unplanned excisions of soft-tissue sarcomas result in increased rates of local recurrence, mainly because of residual tumor [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest unplanned excisions of soft-tissue sarcomas result in increased rates of local recurrence, mainly because of residual tumor [4,10]. While patients with unplanned excisions tend to have superficial tumors, other reports show no adverse impact of unplanned excision on local recurrence [2,13].…”
Section: Introductionmentioning
confidence: 99%